IMPLEMENTATION OF E-CRM IN MACEDONIAN COMPANIES - MARGARITA JANESKA; DEJAN ZDRAVESKI; SUZANA TALESKA; LIDIJA VRSKOSKA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2016)
Customer Relationship Management (CRM) in the digital economy is a challenge for companies that operate in the new electronic environment. In fact, companies that use the internet as basic infrastructure for their operations must adapt and to be ready to respond to the growing challenges who are posed from more sophisticated consumers. CRM concept includes possibilities, methodology and technology that enable companies to operate through improving relations with consumers. CRM as a strategic set of activities begins with a detailed analysis of organizational strategy and ending with measurement of value for stakeholders. CRM owes its expansion to the emergence of the Internet. Digital economy enables more effective targeting and personalization. The basic motive for the research is the fact that e-CRM is a relatively new concept and in recent years has made significant strides in companies around the world aimed at customers. Namely, e-CRM is positioned high on the priority list of today's corporate agendas. The aim of this paper is to consider the importance and benefits of the implementation of e-CRM concept in Macedonia, and to determine the factors that contribute to its successful implementation. The research results should contribute to increasing the profitability and competitiveness of Macedonian companies.